DEFORMATION AND STABILITY ANALYSIS OF DOUBLE-WALL VERTICAL BREAKWATERS FOR EARTHQUAKE RETURN PERIODS - MOHAMED ABOUELNASR (International Journal of Innovations in Engineering Research and Technology, 2021)
Double-wall vertical breakwaters have been widely used during the past centuries, the using of double-wallsections which consist of combined sections have increased because of the progressive elaboration that hasbeen happened in the civil and coastal engineering industry in offshore fields. This paper is discussing thedeformation and the stability analysis for the double-wall vertical breakwaters for several return periods ofearthquake and several breakwaters geometries. One of the advantages of studying stability andserviceability of the double-wall vertical breakwaters for different earthquake return periods, is to ensure thesafety and the clearance spaces for using the suitable area of the double-wall vertical breakwaters as wharfsand as a path for the pipelines in the LPG harbours.